Design and fabricate of micro spray nozzle - Muhammad Syafiq, Razali (2012)
This report shows the design and fabricate of a micro spray nozzle. The objective of the report is to design and fabricate a micro spray nozzle. This report also described the micro spray nozzle which is available among the lecturer or tester or maybe a gardener around the world with its satisfying criteria. Design generation is showed and solid three dimensional structures modelling of the micro spray nozzle was developed with computer aided design software. This report also explains the fabrication process that is needed for this project. Material that is being used in this project is round aluminium hollow metal, rubber hose, nozzle, spray and nozzle connector. The problem encountered during completion of this project is also show in the report. An idea of improvement for the micro spray nozzle is also provided to further improve of the micro spray nozzle. The expected result for this project can solve the entire stated problem statement.